Thermal degradation of typical plastics under high heating rate conditions by TG-FTIR: Pyrolysis behaviors and kinetic analysis. (1st September 2018) - Xu, Fanfan; Wang, Bo; Yang, Dan; Hao, Junhui; Qiao, Yingyun; Tian, Yuanyu
Graphical abstract: Highlights: TG/DTG curve shifts to high temperature zone with the heating rate increases. Thermal degradation of LDPE is similar with PP, but different with PVC. The pyrolysis products are alkanes and alkenes, but PVC also has HCl and aromatics. PVC needs less activation energy than LDPE and PP during the pyrolysis process. The kinetic reaction mechanism of three plastics is different. Abstract: Pyrolysis of plastics has gained more attention recently due to the advantages of environmental protection and energy conversion. In this study, low-density polyethylene (LDPE), polypropylene (PP) and polyvinyl chloride (PVC) were studied under high heating rate conditions to investigate pyrolysis behaviors and find the most suitable kinetic reaction mechanisms. The TG and DTG curves for LDPE were similar to those for PP, but different from those for PVC. It was found that high heating rate led to the shifting of initial, end and peak temperatures to higher values. The FTIR results showed the main products of LDPE and PP were alkanes and alkenes, and the major products of PVC were HCl, alkenes and a small number of aromatic compounds. A comparative study of model-free methods like Ozawa-Flynn-Wall (OFW), Kissinger-Akahira-Sunose (KAS) and Friedman method were discussed to calculate activation energy. Kinetic reaction mechanisms were predicted by using model-fitting methods including Coats-Redfern and Criado method. The pyrolysis reaction mechanism of LDPE was summarized as contracting sphere model, PP was summarized as contracting cylinder model, whereas that of PVC was concluded that two-dimension nucleation for the first stage and three-dimension diffusion (Jander) for the second stage.